Repression of MicroRNA‐372 by Arsenic Sulphide Inhibits Prostate Cancer Cell Proliferation and Migration through Regulation of large tumour suppressor kinase 2. Issue 3 (28th December 2016) - Cao, Hongwen; Feng, Yigeng; Chen, Lei
Abstract: As the main component of realgar, arsenic sulphide (As4 S4 ) contains antitumour activity by repressing cancer cell proliferation and migration in many tumours. However, the detailed mechanism of these processes is not clear yet. MicroRNAs (miRNAs) can function as tumour suppressor or oncogene based on their target mRNAs in different tumour tissues. Here, we found that As4 S4 could repress the overexpression of microRNA‐372 (miR‐372) in two prostate cancer cell lines and its overexpression promoted cell proliferation and migration. Large tumour suppressor kinase 2 (LATS2) was confirmed as a direct target of miR‐372 using luciferase assays in these two prostate cancer cell lines. Down‐regulation of LATS2 could promote prostate cancer cell proliferation and migration just as overexpression of miR‐372 did and overexpression of LATS2 could reverse this effect of miR‐372. The antitumour activity of As4 S4 and the oncogenic function of miR‐372 were further confirmed using a mouse xenograft model. Altogether, our data showed evidence that repressing the overexpression of miR‐372 by As4 S4 could inhibit prostate cancer cell proliferation and migration by targeting LATS2. Therefore, miR‐372 may be a possible biomarker for the prediction of prostate cancer and As4 S4 may have potential therapeutic function for prostate cancer.